Assessments of Dysphagia and Feeding Disorders in Neonates: A Scoping Review Protocol - Flynn, Eadaoin (My University, 2025)
Background: Advances in healthcare have improved the survival rates of critically ill newborns, leading to an increased prevalence of dysphagia and oral feeding difficulties. Premature infants and those with congenital heart disease are particularly at risk, though feeding challenges also occur in otherwise healthy infants. Early identification of dysphagia and/or oral feeding difficulties is essential for timely intervention, but the lack of standardized assessment tools limits objective evaluation. Currently, there is no universally accepted gold standard for assessing neonatal swallowing and feeding function, necessitating a comprehensive review of available diagnostic tools. Objective: This scoping review aims to identify and analyze the characteristics of different assessment methods used to evaluate neonatal swallowing and feeding functions. The review will highlight existing tools, their clinical applications, and gaps in research to inform best practices for healthcare professionals. Methods: The review will follow the PRISMA-ScR framework and JBI methodology for scoping reviews. A systematic search will be conducted in databases including CINAHL, EMBASE, MEDLINE. ClinicalTrials.gov will also be searched for unpublished studies. Data will be extracted and analyzed to identify trends, key assessment areas, and the use of standardized protocols. Findings will be integrated into a written document with charts and tables, identifying gaps in the literature and emerging trends in diagnostic practices. Conclusions: This scoping review will provide a comprehensive synthesis of available neonatal feeding and swallowing assessment tools. By identifying gaps in the literature and highlighting effective diagnostic approaches, the findings will support the development of standardized assessment protocols and improve clinical practice for neonatal dysphagia management.
PRODUCED
Department of Clinical Speech and Language Studies, Trinity College Dublin
Keywords: Dysphagia; Feeding Disorders; Neonates; Evaluation; Scoping Review; DYSPHAGIA; Health